2009
DOI: 10.3897/compcytogen.v3i1.8
|View full text |Cite
|
Sign up to set email alerts
|

Karyotypic analysis of different populations of Carthamus tinctorius Linnaeus (Asteraceae)

Abstract: Abstract. Somatic chromosomes of Carthamus tinctorius L. were analysed. A karyotype formula for each studied population was formulated. Although all samples have 2n = 24, they could be differentiated by their karyotype formula and quantitative parameters of the karyotypes. The chromosomes were assorted into different categories on the basis of arms ratio following Levan et al. (1964). These were further subdivided into different types, on the basis of total length of the chromosomes. Based on an evolutionary p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…Mostly, metacentric and submetacentric chromosomes with variable karyotypic symmetry were reported in species of Passiflora [8]. Primitive nature of the species due to the predominance of metacentric chromosomes was suggested in Carthamus tinctorius [18]. Karyotype analysis revealed significant variations in TF% within the species of P. foetida.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Mostly, metacentric and submetacentric chromosomes with variable karyotypic symmetry were reported in species of Passiflora [8]. Primitive nature of the species due to the predominance of metacentric chromosomes was suggested in Carthamus tinctorius [18]. Karyotype analysis revealed significant variations in TF% within the species of P. foetida.…”
Section: Discussionmentioning
confidence: 92%
“…Significance of seed storage proteins in cultivar differentiation was suggested in species like Cucumis melo and Citrullus lanatus [32] and in Oryza sativa [27]. Karyotype analysis had also been successfully employed in assessing taxonomic relations in the species of Boronia [25], Carthamus tinctorius [18,34], Prunus [14] and in Allium [20]. The technique has been proved useful at intra-specific levels too [19,33,35].…”
Section: Introductionmentioning
confidence: 99%
“…In ancient and primordial plants, symmetric karyotype was found to be predominant, while the asymmetric karyotype was mostly seen in the recent and specialised plants (Jiang et al 2011). Therefore, asymmetric karyotypes are more advanced compared to symmetrical ones (Malik and Srivastava 2009). Symmetric karyotypes were reported by Laura et al (2010) for Lycium species, which were mostly metacentric chromosomes with slight differences in size.…”
Section: Bmentioning
confidence: 95%
“…It was the confirmation of diploid gamete. Malik and Srivastava (2009) demonstrated that treatment with colchicine in Carthamus incited appreciable changes in the diameter of pollen grains, decreased the number of pollen grains per anther and increased pollen sterility. Bragdo (1955) recorded that in the tetraploid of red clover, there was a much greater variation in pollen size and fertility.…”
Section: Discussionmentioning
confidence: 99%